IMPLEMENTATION OF THE COOPERATIVE LEARNING MODEL TYPE MAKE A MATCH TO IMPROVE THE MATHEMATICAL CONCEPT UNDERSTANDING ABILITY IN MULTIPLICATION MATERIAL FOR 2nd STUDENTS - Suryani, Nur Aliah; Ruqoyyah, Siti; Rohaeti, Euis Eti (Journal Of Educational Experts (JEE), 2024)
Including mathematics in primary school curricula is a must. The reality that kindergarteners still have a long way to go before they can grasp basic multiplication concepts. The media and learning methods aren't as appealing, which is the main reason. We propose a cooperative learning model based on the make-a-match algorithm. First, we want to know how well the Cooperative Learning Model Type Make a Match helps second graders grasp multiplication ideas. Second, we want to know what kinds of challenges students have when trying to use this model to increase their learning. three difficulties that educators face while using this paradigm in the classroom. This study used a mixed-methods approach. A one-group pretest and posttest based on a sequential explanatory pre-experimental design is used in this study. Second graders served as the subjects of the study. Research tools include interviews, surveys, and tests. The research results indicate that: (1) there is an improvement in the understanding of multiplication concepts after applying the Model Make a Match, (2) students difficulties in using this model include: difficulty in writing down what is known- asked, lack of understanding of the content story problems, time management, difficulty in concluding discussion results, and difficulty in communicating or presenting discussion results. (3) the challenges teachers face in using this model include: classroom management, generating student interest in reading or understanding the content, lack of familiarity with using the model and time management.